Situational diagnosis of a Basic Health Unit: an experience report (Research, Society and Development, 2021)
This study developed a situational diagnosis of a Basic Health Unit (UBS), which is defined as a set of health actions, in the individual and collective scope, which covers health promotion and protection, disease prevention, diagnosis, treatment, rehabilitation, harm reduction and health maintenance, with the objective of making the Situational Diagnosis of a Basic Health Unit to evaluate the type of population profile. This is an experience report of critical-reflective approach, through a descriptive-comprehensive method, about the Situational Diagnosis of the Basic Health Unit located in Ilha Grande de Santa Isabel, mod.1, in Parnaíba-Piauí, from May, 2021 to August, 2021. It is an exploratory-descriptive and diagnostic-evaluative study, which has used as research instrument the Electronic Citizen's Medical Record (PEC) from the e-SUS.  The experience through the situational diagnosis development, presented benefits for academic formation, as it helps to develop a critical and reflective look at the reality experienced in an UBS from theoretical experiences at the university. Situational diagnosis is an important means of evaluating Basic Health Units, is absolutely necessary for the formation of college students, as it provides understanding of social problems and needs such as: health needs, education, sanitation, security, transport, housing, as well as allowing to know how the health services are organized, being Indispensable to know the problems and strategic situational planning that allows the development of more focused effective health actions related to the problems found.